Durabilidade do concreto com cinza de casca de arroz natural sem moagem: mitigação da reação álcali-sílica e penetração de cloretos - Trindade, Guilherme Höehr (2011)
Natural rice husk ash (RHA) used in concrete contributes to civil construction sustainability. In fact, RHA is considered a residual pollutant and then it is necessary to destine this material correctly. However, it is necessary to investigate the consequences of replacing part of cement by natural RHA to produce concrete for structural purposes. In this context, the aim of this study was to evaluate the concrete durability produced with 15 % of blinder partial replacement by natural RHA in the expansion due to alkali-silica reaction (ASR) and penetration of chloride ion, as well as to suggest preventive measures with the use of mineral additions. In the present study, natural RHA was used as partially replacement of Portland cement. This natural RHA has been obtained without temperature control burning and placed directly into the mixer to suffer self-grinding with aggregates. We investigated the RAS neutralization of natural RHA by the use of cement with mineral additions (CPIIZ, CPIII e CPIV), as well as, we performed additional replacements of part from CPIIZ cement by fly ash (10, 15, 20, 30 and 40 %). We employed accelerated expansion method at 80°C in mortar bars followed by scanning electron microscopy (SEM) and X-ray diffraction (XRD), and long term at 38 °C and accelerated at 60 °C methods in concrete prisms. To investigate concrete resistance in the chloride ion penetration, we used chloride ions penetration method by immersion in saline solution (CPT) of concrete produced with natural RHA and CPIIZ cement added of fly ash (0, 12.75 or 17 %) and water-binder ratios of 0.45, 0.55 and 0.65 were adopted. Analyses of results were based in slope (K ) obtained from the average depths of penetration. In this study, we verified that in mortar bars assay the natural RHA generated expansion above of results allowed by norm in mixtures with standard cement, while CPIIZ cement with addition from 20 % of fly ash showed to mitigate the ASR. These results demonstrated that effect of mitigation of RAS proportionally increased with fly ash addition. Moreover, CPIV cement demonstrated excellence in mitigate the expansive reaction. The SEM analysis identified the characteristic products of ASR in the samples containing natural RHA. XRD analysis showed that the samples of mixtures with higher content of mineral addition showed peaks of calcium hydroxide (CH) with less intensity and mixtures with natural RHA presented greater calcium carbonate content. In relation to concrete prisms molded at 60°C, results showed an increase in expansion for mixture of CPIIZ with natural RHA, but these results remained below of maximum expansion predicted by test. Mixtures of CPII-Z with natural RHA added of 10 and 15% fly ash demonstrated better efficiency in expansion mitigation. In relation to concrete prisms molded at 38°C, the results are not conclusive to 12 months, but mixtures that presented a great expansion were of CPII-Z with natural RHA and 15% fly ash, the CPII-Z with RHA natural and CPII-Z with natural RHA and 10% fly ash, respectively. However, all mixtures had expansion below the maximum limit suggested by the Brazilian standard at 24 months. Through of results CPT, we can conclude that mineral additions provided improvements to the concrete with higher ages due to pozzolanic effect. Moreover, the best results obtained were in trace with lowest water-binder ratios, probably due to increased consumption of cement, which increases the CH amount to interact with the RHA and the fly ash. Therefore, mixtures of Portland cement with fly ash and natural RHA meet the durability of concrete, and also the use of natural RHA would be an important contribution to sustainability and preservation of environment by civil construction.